Short communication: Relationship between the level of bovine leukemia virus antibody and provirus in blood and milk of cows from a naturally infected herd - Jaworski, Juan Pablo (2016)
We explored the relationship between the level of bovine leukemia virus antibodies and provirus load during natural infection. For that purpose, a set of 50 blood and milk paired samples were analyzed for the presence of bovine leukemia virus provirus and antibodies. Additionally, provirus load and antibody titers were measured and the relationship between these variables was investigated. Bovine leukemia provirus was detected in 59% of milk samples and a negative correlation was observed between the level of milk provirus load and milk antibody titers. By the consumption of raw milk, calves might be exposed to bovine leukemia virus favoring the perinatal transmission of this disease